14j+68=56j-100

Simple and best practice solution for 14j+68=56j-100 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14j+68=56j-100 equation:


Simplifying
14j + 68 = 56j + -100

Reorder the terms:
68 + 14j = 56j + -100

Reorder the terms:
68 + 14j = -100 + 56j

Solving
68 + 14j = -100 + 56j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-56j' to each side of the equation.
68 + 14j + -56j = -100 + 56j + -56j

Combine like terms: 14j + -56j = -42j
68 + -42j = -100 + 56j + -56j

Combine like terms: 56j + -56j = 0
68 + -42j = -100 + 0
68 + -42j = -100

Add '-68' to each side of the equation.
68 + -68 + -42j = -100 + -68

Combine like terms: 68 + -68 = 0
0 + -42j = -100 + -68
-42j = -100 + -68

Combine like terms: -100 + -68 = -168
-42j = -168

Divide each side by '-42'.
j = 4

Simplifying
j = 4

See similar equations:

| (6x^2+15x+4)/(x+2) | | 26x+16=51x-34 | | 8b+49=13b-91 | | 4y+3/5=3/4 | | 189/4 | | Y=8X^2-X-6 | | fx(6)=4x-2 | | 8a-24z= | | -1/4=189.5 | | 7x^2+5x-h=0 | | 4y=6/9 | | -2-2=-6+x | | 18x+6-21-2x= | | F(X)=-6X-3+X(3X-7) | | (2w-3y)*(2w+7)= | | y=15/y+2y/10 | | (s^2-10s+16)/(s+2) | | 5b-6-12b-8= | | K=(s^2-10s+16)/(s+2) | | 0,5^5-5x/2x-31 | | 50-40x=50 | | 41-x=3(5x+3) | | F(X)=3X-4+X(9X-7) | | 3h^2-60=24h | | 9y+5x=10 | | y=11x^2+5x+13 | | 3h+9=4h-3 | | c+3=15-3c | | (x-80)/X=0.2 | | 4(2x-4)=8x+56 | | 4(2x-4)=8x+36 | | 4(2x-4)=8x+20 |

Equations solver categories